Influence of the Water Content of Foreshore Sediments in the Tidal Morphological Construction Process in Port-Bouët and Assouindé Coastal Sectors, Côte-d'Ivoire - Mathurin, SAIMON Aby Atsé; Mamadou, TOURE; Blandine, EGORAN Akissi; Edith-Thérèse, KOUABENA Kossia (Research Advances in Environment, Geography and Earth Science Vol. 10, 2024)
Côte d'Ivoire's 566 km coastline backs onto the Atlantic Ocean. This shapes the coastline under unusual storm swell conditions, with those recorded since 1984 having significant heights of between 2.10 and 2.7 m. These swells shape the coastline in spectacular retreats, usually within one or two tides. The aim of this study is to understand the influence of subsurface sediment water content on foreshore morphology. The study of the influence of subsurface water saturation rate on aerial morphology was carried out on the coarse-grained (784.46 µm) Port-Bouët and fine-grained (231.96 µm) Assouindé shorelines. Knowledge of tidal shoreline morphologies on microtidal coasts such as those of Côte d'Ivoire reveals two trends: (i) erosion of the foreshore near the high tide and accretion near the low tide or (ii) accretion of the foreshore near the high tide and erosion near the low tide. The sediment load that is enriched or eroded varies from one part of the foreshore to another. The contribution of hydrodynamic parameters, in particular the significant height of the swell and the theoretical tide, explains these trends, but not in an exhaustive way. The water content in the sediment was analysed to understand its impact on the shoreline morphologies resulting from the action of hydrodynamic forcing. Moisture content also has a positive impact on the erosion resistance of finer soils and a negative effect on the erosion resistance of coarse-grained soils. In this study, in which two facies were examined, fine and coarse sands, clear-cut erosion was observed for water-saturated coarse sands and less clear-cut erosion for saturated fine sands. Similar results were obtained in the present study. To this end, two altimetric surveys synchronised with sedimentological monitoring of the submerged foreshore in coarse sand facies and fine sand facies were carried out at Port Bouët and Assouindé on the east coast of Côte d'Ivoire. These surveys indicate that erosion occurs at times of high water content when saturation of the sediment is reached. This observation is clearly expressed on coarse sand facies, but less so on fine sand facies. The latter is more able to absorb water and is therefore less vulnerable to erosion of the foreshore. The water masses required to saturate 100g of fine sand are almost identical, reflecting virtually identical resistance to erosion. This could explain the almost similar morphologies observed on the Assouindé coastline, with little variation in the cross-shore and long-shore directions.